Study of dust color temperature and visual extinction distribution of a far infrared cavity at 60 and 100 µm IRAS map around the AGB star at galactic latitude 8.6⁰ - Gautam, A K; Aryal, B (BIBECHANA, 2020)
The dust-grain structure in the far infrared region under IRAS (Infrared Astronomical Satellite) Survey was studied using sky view virtual observatory. In order to find the possible far infrared cavity, we used SIMBAD database. In this paper, we discuss about the dusty environment of a far infrared cavity around the AGB star located at R.A. (J2000) =01h 41m 01s and Dec (J2000) = 71o 04’ 00” lying within far infrared loop G125+09 in the far infrared IRAS maps. A cavity like structure (major diameter ∼ 2.55 pc & minor diameter ∼ 0.77 pc) is found to lie at R.A. (J2000)= 01h 46m 57.2s and DEC (J2000)= 71o 24’ 57.1”, located at a distance ∼ 220 pc from the star. We studied the distribution of flux density, dust color temperature, dust mass, inclination angle, visual extinction and FIR spectral distribution of the cavity. We further studied the distribution of Planck function along extension and compression. The dust color temperature is found to lie in the range (19.7±0.65) K to 21.1±0.35) K which shows the cavity is isolated and stable. Product of visual extinction and dust color temperature is found to be less than one. A possible explanation of the results will be discussed. BIBECHANA 17 (2020) 42-49